Negotiation and erosion of born again prestige in Nairobi - Gez, Y. N.; Droz, Y. (Nova Religio, 2015)
The social and political efficacy of ‘‘Born-Again’’ identity in Nairobi is fed by the accumulation of personal prestige or symbolic capital emerging from the Born-Again actor’s association with religious and moral virtues. However, this prestige is being undermined by ongoing rumors and scandals, risking disruption of the benefits associated with this morality. In this article, we explore the popular discontent with Born-Again identity and practice, concluding that its prestige in Nairobi is possibly eroding, with risk to its efficacy in mobilizing social and political power.